PENERAPAN RESTORATIF JUSTICE DALAM PENYELESAIAN TINDAK PIDANA DI KESATUAN RESKRIM POLRES KUBU RAYA - LISAN PURA NIM. A1012171206 (Jurnal Fatwa Hukum, 2023)
Abstrac With Police Regulation Number 8 of 2021 concerning handling criminal acts based on restorative justice, police officers have a legal umbrella in carrying out settlement of cases based on restorative justice. With the existence of regulations that have been issued by the police institution, it will certainly make it easier for the police to carry out their duties to resolve criminal cases. In general, the handling of criminal cases reported to the Police will be followed up and handled by Investigators and assistant investigators at the Criminal Investigation Unit, from the receipt of the police report until the case can be resolved. How is the readiness of the Police themselves to carry out the formula for solving criminal cases with the concept of restorative justice, and what are the obstacles faced by the Police with the form of restorative justice solutions    As for the formulation of the problem in this study are: How is the application of restorative justice in resolving criminal acts in the Criminal Investigation Unit of the Kubu Raya Police; Why is the implementation of restorative justice in resolving criminal acts at the Kubu Raya Police Criminal Investigation Unit encountered problems?The research carried out is empirical juridical research or a type of sociological legal research, carried out on actual conditions or real situations that occur in society with the aim of knowing and finding the facts and data needed, after the required data is collected then it goes to the identification of the problems that will be investigated. finally got to solving the problem.The Police to maximize the completion of Restorative Justice by always providing explanations to the public, especially those involved in criminal law cases that there are other legal remedies outside the court such as the principle of Restorative Justice which has a very good impact on victim justice. That the concept of justice is not merely how all claims for material compensation from victims can be fulfilled at the time of mediation, but other alternatives can be found that are acceptable to both parties. Then the participation of the community itself where every resolution is expected to always be involved by always establishing communication between the police and community leaders to solve any legal problems that exist in the communityKeywords: Application of Law, Restorative Justice, Misdemeanors Abstrak Dengan adanya Peraturan Polisi Nomor 8 tahun 2021 tentang penanganan tindak pidana berdasarkan keadilan restoratif, aparat Kepolisian mempunyai payung hukum dalam menjalankan penyelesaian perkara berdasarkan Keadilan Restoratif. Dengan adanya peraturan yang telah dikeluarkan oleh lembaga kepolisian tersebut tentunya akan lebih mempermudah aparat kepolisian dalam menjalankan tugasnya untuk menyelesaikan perkara tindak pidana. Penanganan perkara pidana yang dilaporkan di Kepolisian pada umumnya akan ditindak lanjuti dan tangani oleh Penyidik dan penyidik pembantu di Satuan Reserse Kriminal, dari mulai diterimanya laporan polisi hingga perkara tersebut dapat diselesaikan.  Bagaimana kesiapan dari pihak Kepolisian sendiri melaksanakan rumusan penyelesaian perkara pidana dengan konsep restoratif justice, serta apa saja kendala-kendala yang dihadapi oleh Pihak Kepolisian dengan bentuk penyelesaian restoratif justice    Adapun yang menjadi rumusan masalah didalam penelitian ini adalah: Bagaimana penerapan restoratif justice dalam menyelesaikan tindak pidana di Satuan Reserse Kriminal Polres Kubu Raya; Mengapa penerapan restoratif justice dalam menyelesaikan tindak pidana di Satuan Reserse Kriminal Polres Kubu Raya terdapat kendala?       Penelitian yang dilakukan adalah penelitian yuridis empiris atau jenis penelitian hukum sosiologis, dilakukan terhadap keadaan sebenarnya atau keadaan nyata yang terjadi di masyarakat dengan maksud untuk mengetahui dan menemukan fakta-fakta dan data yang dibutuhkan, setelah data yang dibutuhkan terkumpul kemudian menuju kepada identifikasi masalah yang pada akhirnya menuju pada penyelesaian masalah.Pihak Kepolisian untuk memaksimalkan penyelesaian secara Restoratif Justice dengan selalu memberikan penjelasan kepada masyarakat khususnya yang terlibat perkara hukum pidana bahwa ada upaya hukum lain diluar pengadilan seperti prinsip Restoratif Justice yang dampaknya sangat baik untuk keadilan korban. Bahwa konsep keadilan bukan semata-mata bagaimana semua tuntutan ganti rugi materi dari korban dapat terpenuhi pada saat mediasi tersebut namun dapat dicarikan alternatif lain yang dapat diterima oleh kedua belah pihak.   Kemudian partisipasi dari masyarakat itu sendiri dimana setiap penyelesaian diharapkan selalu dilibatkan dengan selalu menjalin komunikasi antara pihak kepolisian dan tokoh masyarakat guna memecahkan setiap permasalahan hukum yang ada di masyarakatKata Kunci : Penerapan Hukum, Restoratif Justice, Pidana Ringan